A Comprehensive Phylogeny Reveals Functional Conservation of the UV-B Photoreceptor UVR8 from Green Algae to Higher Plants - Fernández, María B.; Tossi, Vanesa; Lamattina, Lorenzo; Cassia, Raúl (Frontiers in Plant Science, 2016)
Ultraviolet-B (UV-B) is present in sunlight (280–315 nm) and has diverse effects on living organisms. Low fluence rate of exposure induces a specific photomorphogenic response regulated by the UV-B response locus 8 (UVR8) receptor. UVR8 was first described in Arabidopsis thaliana. In the absence of stimuli it is located in the cytoplasm as a homodimer. However, upon UV-B irradiation, it switches to a monomer and interacts with the ubiquitin ligase E3 COP1 via the UVR8 β-propeller domain and the VP core. This induces the expression of the transcription factor HY5 leading to changes in the expression of genes associated with UV-B acclimation and stress tolerance. UVR8 senses UV-B through tryptophan residues being Trp233 and 285 the most important. Based on the comparison and analysis of UVR8 functionally important motifs, we report a comprehensive phylogeny of UVR8, trying to identify UVR8 homologs and the ancestral organism where this gene could be originated. Results obtained showed that Chlorophytes are the first organisms from the Viridiplantae group where UVR8 appears. UVR8 is present in green algae, bryophytes, lycophytes, and angiosperms. All the sequences identified contain tryptophans 233 and 285, arginines involved in homodimerization and the VP domain suggesting they are true UVR8 photoreceptors. We also determined that some species from bryophytes and angiosperms contain more than one UVR8 gene copy posing the question if UVR8 could constitute a gene family in these species. In conclusion, we described the functional conservation among UVR8 proteins from green algae to higher plants.